The Role of Green Marketing in Toyota’s Costs Reduction - Mimoune, Mouaad; Bouzida, Saoussen (Finance and Business Economies Review, 2019)
In order to clarify to the ambiguity surrounding the concept of green marketing and its ability to create economic gains, especially with regard to the potential costs of the transformation process, which may increase the burden of the organization and reduce its competitive advantages. Considering that most business organizations still worried about the economic feasibility of green marketing. This paper aims is to examine the role of green marketing adoption in reducing overall costs in the business organization. The study concluded that Toyota's adoption of green marketing in the context of reducing the total costs , through a three environmental entrances , allowed the organization a significant number of profits.